Fishing for happiness: The effects of generating positive imagery on mood and behaviour - Pictet, A; Coughtrey, A; Mathews, A; Holmes, E (2011)
Experimental evidence using picture-word cues has shown that generating mental imagery has a causal impact on emotion, at least for images prompted by negative or benign stimuli. It remains unclear whether this finding extends to overtly positive stimuli and whether generating positive imagery can increase positive affect in people with dysphoria. Dysphoric participants were assigned to one of three conditions, and given instructions to generate mental images in response to picture-word cues which were either positive, negative or mixed (control) in valence. Results showed that the positive picture-word condition increased positive affect more than the control and negative conditions. Participants in the positive condition also demonstrated enhanced performance on a behavioural task compared to the two other conditions. Compared to participants in the negative condition, participants in the positive condition provided more positive responses on a homophone task administered after 24 h to assess the durability of effects. These findings suggest that a positive picture-word task used to evoke mental imagery leads to improvements in positive mood, with transfer to later performance. Understanding the mechanisms underlying mood change in dysphoria may hold implications for both theory and treatment development. © 2011 Elsevier Ltd.